2010
DOI: 10.1016/j.atherosclerosis.2009.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and recycling properties of an apolipoprotein mimetic peptide, Ac-hE18A-NH2

Abstract: Apolipoprotein E (apoE) exerts prominent anti-inflammatory effects and undergoes recycling by target cells. We previously reported that the peptide, Ac-hE18A-NH2, composed of the receptor binding domain (LRKLRKRLLR) of apoE covalently linked to the Class A amphipathic peptide 18A, dramatically lowers plasma cholesterol and lipid hydroperoxides and enhances paraoxonase activity in dyslipidemic animal models. The objective of this study was to determine whether this peptide, analogous to apoE, exerts anti-inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 44 publications
3
53
0
Order By: Relevance
“…While Ac-hE18A-NH 2 is rapidly cleared from the circulation after IV administration, it continues to exert signifi cant benefi cial effects on aortic lesions for up to a month after suspending peptide administration in mouse models of atherosclerosis ( 135 ). Subsequent studies revealed that Ac-hE18A-NH 2 induces the release of PON-1 and lipid-poor pre ␤ -HDL particles from hepatocytes and also promotes apoE secretion from hepatocytes and macrophages ( 131,133,136,137 ). These studies further showed that Ac-hE18A-NH 2 is recycled by cells, thus enabling the potentiation and prolongation of its anti-atherogenic and anti-infl ammatory effects ( 131 ).…”
Section: Anti-atherogenic and Anti-inflammatory Effects Of Ac-he18a-nhmentioning
confidence: 95%
See 2 more Smart Citations
“…While Ac-hE18A-NH 2 is rapidly cleared from the circulation after IV administration, it continues to exert signifi cant benefi cial effects on aortic lesions for up to a month after suspending peptide administration in mouse models of atherosclerosis ( 135 ). Subsequent studies revealed that Ac-hE18A-NH 2 induces the release of PON-1 and lipid-poor pre ␤ -HDL particles from hepatocytes and also promotes apoE secretion from hepatocytes and macrophages ( 131,133,136,137 ). These studies further showed that Ac-hE18A-NH 2 is recycled by cells, thus enabling the potentiation and prolongation of its anti-atherogenic and anti-infl ammatory effects ( 131 ).…”
Section: Anti-atherogenic and Anti-inflammatory Effects Of Ac-he18a-nhmentioning
confidence: 95%
“…1 ) ( 93, 122 ). The peptide was able to mediate cholesterol effl ux independently of ABCA1 and had the additional advantage of facilitating cholesterol clearance due to the presence of the receptor binding domain ( 131 ). In vivo administration of Ac-hE18A-NH 2 has been shown to reduce plasma cholesterol in mouse and rabbit models of atherosclerosis ( 122,132,133 ).…”
Section: Anti-atherogenic and Anti-inflammatory Effects Of Ac-he18a-nhmentioning
confidence: 99%
See 1 more Smart Citation
“…The peptide stimulated cholesterol efflux similar to native proteins on a molar basis and reduced atherosclerosis in hyperlipidemic mice. Currently, this compound has entered clinical development (Artery Therapeutics, Danville, CA) [55]. A different peptide, a 10-amino acid long oral peptide derived from apoJ is termed D-[113-122] apoJ containing a class G*-helix.…”
Section: Apoa-1 Mimetic Peptidesmentioning
confidence: 99%
“…The ability of plasma from peptide-treated and control animals to promote monocyte adhesion to endothelial cells was assessed by bovine aortic endothelial cell (BAEC) assay ( 7,23 ). BAEC were grown to 80% confl uency in 24-well plates.…”
Section: Monocyte Adhesion Assaysmentioning
confidence: 99%